2020
DOI: 10.32641/rchped.v91i2.1156
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic variability in infants admitted to Latin-American pediatric intensive units due to acute bronchiolitis

Abstract: Objetivo: describir las terapias utilizadas en lactantes con bronquiolitis aguda admitidos en 20 Unidades de Cuidados Intensivos (UCI) pediátricos miembros de LARed en 5 países latinoamericanos.Pacientes y Método: Estudio observacional retrospectivo, multicéntrico, de datos del Registro Latinoamericano de Falla Respiratoria Aguda Pediátrica. Se incluyeron niños menores de 2 años ingresados a UCI pediátrica por bronquiolitis aguda comunitaria entre mayo-septiembre 2017. Se recolectaron datos demográficos, clíni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
3
0
5
Order By: Relevance
“…The intubation rate in our study is higher than in previous studies [4,[22][23][24], while our re-intubation rate is comparable to previously reported re-intubation rates [25,26]. A largescale observational study in Australia reported a 37% intubation rate in children admitted to the PICU in 2002 [4].…”
Section: Discussionsupporting
confidence: 70%
“…The intubation rate in our study is higher than in previous studies [4,[22][23][24], while our re-intubation rate is comparable to previously reported re-intubation rates [25,26]. A largescale observational study in Australia reported a 37% intubation rate in children admitted to the PICU in 2002 [4].…”
Section: Discussionsupporting
confidence: 70%
“…Fifth, our score is most applicable at institutions similar to these 128 centers. Although our demographics, MV usage, and outcomes are similar to cohorts from around the globe (1,25,(30)(31)(32), generalizability to ICUs with more ill patient populations, unique practices, or distinctive ICU admission criteria may be limited. In addition, applicability at institutions where HFNC is used on the wards may vary.…”
Section: Discussionmentioning
confidence: 92%
“…Another factor in the low infection rate among pediatric healthcare workers is the usual seasonal epidemic of viral respiratory infections. Every winter, we face a sudden increase in up to 400% of children with acute respiratory failure due to respiratory viruses [ 33 ]. Our greatest strengths are the interventions aimed at preventing respiratory failure progression, balancing the risks of overtreatment and futile treatments, and delaying lifesaving therapies, like MV.…”
Section: Discussionmentioning
confidence: 99%